(untitled) (Global Journal of Human-Social Science, 2023)
Despite media significance a lot still needs to be learned about how women s bodies are re presented in media narratives and the ensuing implications of these representations for women s health The construction of a uniform socio-culturally feminine image regime of truth owing to the feminine body shape standard evolved due to mainstream Western media s fascination with a slender female physique Aapola et al 2005 In our culture those who do not adhere to such aesthetic standards are often left out of discussions about feminine identity Duncan 1994